2014
DOI: 10.1093/jjco/hyu053
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Mutation Status in Japanese HER2-negative Breast Cancer Patients

Abstract: This study aimed to develop a nomogram to predict fluorescence in situ hybridization (FISH) assay results for HER2-borderline breast cancer as determined via immunohistochemistry (IHC) among patients in China. We reviewed a database of breast cancer patients diagnosed between January 2007 and April 2013 at our institutions. We used logistic regression to develop a nomogram and we used receiver operating characteristic curve analysis and calibration plots to validate our nomogram. In total, 1138, 301 and 344 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Regarding the other mutations found in our series, the p.I767M mutation was also not functionally characterized as oncogenic, but appeared sensitive to conventional anti-ERBB2 drugs (trastuzumab, lapatinib, neratinib) [14]; the p.S310Y mutation has been functionally characterized as activating mutations that sensitize cancer cells to ERBB2 inhibitors [13]. Interestingly, the mutational spectrum of ERBB2 of ILC reported in this study is distinct from that reported previously by studies carried out on Asian populations, suggesting a possible influence of ethnic factors on the ERBB2 mutation spectrum [24, 27, 28]. Notably, a case-report described the spectacular response to lapatinib for a metastatic ILC patient harboring a rare ERBB2 mutation (p.L869Q) [17].…”
Section: Discussionmentioning
confidence: 70%
“…Regarding the other mutations found in our series, the p.I767M mutation was also not functionally characterized as oncogenic, but appeared sensitive to conventional anti-ERBB2 drugs (trastuzumab, lapatinib, neratinib) [14]; the p.S310Y mutation has been functionally characterized as activating mutations that sensitize cancer cells to ERBB2 inhibitors [13]. Interestingly, the mutational spectrum of ERBB2 of ILC reported in this study is distinct from that reported previously by studies carried out on Asian populations, suggesting a possible influence of ethnic factors on the ERBB2 mutation spectrum [24, 27, 28]. Notably, a case-report described the spectacular response to lapatinib for a metastatic ILC patient harboring a rare ERBB2 mutation (p.L869Q) [17].…”
Section: Discussionmentioning
confidence: 70%
“…Patients with HER-2-mutant NSCLC were also reported to have achieved disease control with anti-HER-2 therapy [108,109]. Similar outcome of HER-2-targeted therapy has also been achieved in breast cancer patients with HER-2-mutantions [103,110]. Notably, in Bose's research, all HER-2 mutations including mutation L755S which is resistant to lapatinib, exhibited sensitivity to the irreversible HER-2 inhibitor, neratinib [23].…”
Section: The Therapy Methods To These Her-2 Mutationsmentioning
confidence: 96%
“…Human epidermal growth factor receptor 2 somatic mutations were initially identified in the tyrosine kinase domain of the HER2 gene in breast cancer patients in 2006 . Recently, such mutations have been identified in HER2‐negative breast cancer patients by sequencing assays, including whole‐cancer genome sequencing . Although the mutation rate of this gene is very low (<2%), in vitro and in vivo experiments have shown that some somatic mutations can activate the HER2 signaling pathway in HER2‐negative cells and that these cells are sensitive to some HER2‐targeted drugs .…”
mentioning
confidence: 99%
“…(14) Recently, such mutations have been identified in HER2-negative breast cancer patients by sequencing assays, including whole-cancer genome sequencing. (14)(15)(16)(17)(18)(19)(20)(21) Although the mutation rate of this gene is very low (<2%), in vitro and in vivo experiments have shown that some somatic mutations can activate the HER2 signaling pathway in HER2-negative cells and that these cells are sensitive to some HER2-targeted drugs. (22)(23)(24)(25) These findings suggest that HER2 somatic mutations represent an alternative mechanism for the activation of HER2 in HER2-negative breast cancers, raising an interesting question of whether somatic mutations in HER2-negative breast cancer patients influence the clinical outcome.…”
mentioning
confidence: 99%